Long Tandem Arrays of Cassandra Retroelements and Their Role in Genome Dynamics in Plants - Kalendar, Ruslan; Raskina, Olga; Belyayev, Alexander; Schulman, Alan H (International journal of molecular sciences, 2020)
Retrotransposable elements are widely distributed and diverse in eukaryotes. Their copy number increases through reverse-transcription-mediated propagation, while they can be lost through recombinational processes, generating genomic rearrangements. We previously identified extensive structurally uniform retrotransposon groups in which no member contains the gag, pol, or env internal domains. Because of the lack of protein-coding capacity, these groups are non-autonomous in replication, even if transcriptionally active. The Cassandra element belongs to the non-autonomous group called terminal-repeat retrotransposons in miniature (TRIM). It carries 5S RNA sequences with conserved RNA polymerase (pol) III promoters and terminators in its long terminal repeats (LTRs). Here, we identified multiple extended tandem arrays of Cassandra retrotransposons within different plant species, including ferns. At least 12 copies of repeated LTRs (as the tandem unit) and internal domain (as a spacer), giving a pattern that resembles the cellular 5S rRNA genes, were identified. A cytogenetic analysis revealed the specific chromosomal pattern of the Cassandra retrotransposon with prominent clustering at and around 5S rDNA loci. The secondary structure of the Cassandra retroelement RNA is predicted to form super-loops, in which the two LTRs are complementary to each other and can initiate local recombination, leading to the tandem arrays of Cassandra elements. The array structures are conserved for Cassandra retroelements of different species. We speculate that recombination events similar to those of 5S rRNA genes may explain the wide variation in Cassandra copy number. Likewise, the organization of 5S rRNA gene sequences is very variable in flowering plants; part of what is taken for 5S gene copy variation may be variation in Cassandra number. The role of the Cassandra 5S sequences remains to be established.
Keywords: molekulární evoluce; ectopic recombination; rostliny; rekombinace genetická; konformace nukleové kyseliny; Genome, Plant; Nucleic Acid Conformation; genomika; Chromosomes, Insect; Recombination, Genetic; Moths; genom rostlinný; Retroelements; Cassandra TRIM; retroelementy; genome evolution; Plants; Terminal Repeat Sequences; můry; RNA, Ribosomal, 5S; Animals; zvířata; koncové repetice; Genomics; chromozomy hmyzu; fylogeneze; Host-Parasite Interactions; interakce hostitele a parazita; 5S RNA gene; RNA ribozomální 5S; retrotransposon; Phylogeny; long tandem array; Evolution, Molecular